2017
DOI: 10.1186/s12906-017-1826-9
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at LI11 promotes jejunal motility via the parasympathetic pathway

Abstract: BackgroundGastrointestinal motility disorder has been demonstrated to be regulated by acupuncture treatment. The mechanisms underlying the effects of acupuncture stimulation of abdominal and lower limb acupoints on gastrointestinal motility have been thoroughly studied; however, the physiology underlying the effects of acupuncture on the forelimbs to mediate gastrointestinal motility requires further exploration. The aim of this study was to determine whether electroacupuncture (EA) at LI11 promotes jejunal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The role of the somatoautonomic reflex, which was demonstrated by Sato and his colleagues in the 1960s[ 34 , 35 ], is now considered the neurological basis of acupuncture in GI motility modulation[ 36 , 37 ], and this modulation exerts a regional-specific effect[ 38 , 39 ] (Figure 1 ). Stimulating acupoints in the abdominal area inhibits gastric, duodenal, and jejunal motility by increasing sympathetic efferent fiber activity, and stimulating acupoints in the limb, which, in contrast, facilitates the above-mentioned gut motility by exciting vagal efferent fiber activity[ 18 , 40 - 43 ]. The effect of acupuncture on GI motility could be attenuated by vagotomy or sympathectomy[ 16 , 44 - 46 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
“…The role of the somatoautonomic reflex, which was demonstrated by Sato and his colleagues in the 1960s[ 34 , 35 ], is now considered the neurological basis of acupuncture in GI motility modulation[ 36 , 37 ], and this modulation exerts a regional-specific effect[ 38 , 39 ] (Figure 1 ). Stimulating acupoints in the abdominal area inhibits gastric, duodenal, and jejunal motility by increasing sympathetic efferent fiber activity, and stimulating acupoints in the limb, which, in contrast, facilitates the above-mentioned gut motility by exciting vagal efferent fiber activity[ 18 , 40 - 43 ]. The effect of acupuncture on GI motility could be attenuated by vagotomy or sympathectomy[ 16 , 44 - 46 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
“…As stated, EA regulates gastrointestinal motility via the vagus and sympathetic nerves. Studies have shown that injection of the M receptor blocker atropine can inhibit the gastric motility-promoting effect of EA at LI11 (Quchi)[25], and the injection of the beta blocker propranolol can abrogate the inhibition of jejunal motility[26]. However, due to a poor specificity of the blockers, the specific receptor subtype(s) through which these effects are mediated is not clearly known.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture was performed at the forelimb LI11 (Quchi) acupoint by inserting a pair of stainless-steel acupuncture needles (diameter: 0.3 mm) up to 3 mm in depth at each site. LI11 is located midway between the lateral end of the transverse cubital crease and the lateral humeral epicondyle ( 17 ). The needles were connected to Han’s electroacupuncture instrument (LH402A; Beijing Huawei Technologies Co. Ltd).…”
Section: Methodsmentioning
confidence: 99%